Holocene environmental change and the vegetation community dynamics of the Kynsna forest : pollen and charcoal analysis of sediments from Groenvlei, Southern Cape, South Africa - Duncan, C E (Department of Environmental and Geographical Science, 2014)
Includes bibliographical references.